"Law-and-Economics" in Commercial Law Settings - Kanda, Hideki (The Sociology of Law, 1993)
Despite the increased popularity of the "law-and-economics" approach in the commercial law area in the past years in the U.S., it remains inactive in the Japanese academic circle. The natural emphasis on economic efficiency in the law-and-economics scholarship has not attracted Japanese scholars in the commercial law area. Overemphasizing an efficiency criterion is not illuminating even in the commercial law area, in which players act in economic terms rather than with some other "social" norms. But underemphasizing the law-and-economic approach leads to misunderstanding the correct roles of commercial law. While commercial law scholars generally have not shown their interest in an interdisciplinary approach, including "law- and -sociology" and "law- and- economics", law- and -sociology scholars too have been inactive in undertaking research on topics in commercial law. Thus, perhaps commercial law studies in Japan have been isolated from other areas in the sense that no interdisciplinary approach has been attempted. Given the influence of the U.S. scholarship in this area, it is fair to say that the present Japanese situation will gradually change in the future yet, it is difficult to predict when such an approach, the law-and-economics one in particular, will be popularly employed in the commercial law area in Japan.